Pendidikan, Pendapatan Kepala Keluarga Dengan Perilaku Hidup Bersih Dan Sehat - Eny Retna Ambarwati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: Health is a human right and is a human resource investment, and has contributed greatly to improving the Human Development Index (HDI). Healthy conditions can be achieved by changing unhealthy behaviors to healthy behaviors and creating a healthy environment at home. Efforts to increase healthy behaviors in the household have not indicated an optimal result. In addressing the health problems that occur in families, who make the decisions concerning the solution to the problems is still the family head or the elder family member, it is they who will determine the problems and the needs of the family.Objective: To examine whether there is a relationship between education and income of the family head and the clean and healthy living behaviors in the order of the households in Kwasen village Srimartani Piyungan Bantul.Method: The analytical observational research with design in this research uses cross-sectional approaches. The population of this research was all the family heads who reside in the Kwasen village, Srimartani, Piyungan, Bantul. The sampling technique used was exhaustive sampling method. The analysis employed was univariate analysis using frequency distributions, and bivariate analysis using the chi square (X2).Result: The results of this research indicate a significant relationship between education and incomes of the family heads with PHBS in the order of households in Kwasen village, Srimartani, Piyungan, Bantul. Concerning the education of the family heads, majority of them graduated from junior high school - senior high school which was as many as 164 (46.59%) KKs, and followed by the family heads who did not go to school/ graduated from elementary school which was as many as 128 (36.36%) KKs, while the minority of them who graduated from college was as many as 60 (17.05%) KKs. The majority of the family heads having incomes < UMR (minimum regional wage) were as many as 219 (62.22%) KKs and the minorities having incomes ≥ UMR were as many as 133 (37.78%) KKs. The family heads with healthy PHBS II were as many as 167 (47.40%) KKs followed by as many as 167 (47.40%) KKs of healthy PHBS III, healthy PHBS IV as many as 71 (20.20%) KKs, and minority family heads of healthy PHBS I as many as 2 (0.60%) KKs.Conclusion: There is a relationship between education and income on the clean and healthy living behaviors.Keywords : Education, Income, PHBS